2020
DOI: 10.1111/obr.13055
|View full text |Cite
|
Sign up to set email alerts
|

The role of adipokines in the modulation of lymphoid lineage cell development and activity: An overview

Abstract: Summary Adipokines are predominantly known to play a vital role in the control of food intake, energy homeostasis and regulation of glucose and lipid metabolism. However, evidence supporting the concept of their extensive involvement in immune system defence mechanisms and inflammatory processes continues to grow. Some of the adipokines, that is, leptin and resistin, have been recognized to exhibit mainly pro‐inflammatory properties, whereas others such as visfatin, chemerin, apelin and vaspin have been found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 160 publications
(198 reference statements)
1
6
0
Order By: Relevance
“…Although some factors that have been traditionally linked to poor immune recovery are being investigated [3,5,24,28], the complete mechanism preceding ART-associated poor immune recovery remains unclear. On the basis of previous results [10,12,[29][30][31], we trust that adipokines may play a key role in immune reconstitution in PLHIV. Indeed, in this study, we postulated that low baseline circulating apelin receptor and ZAG concentrations were related to low CD4 + T-cell reconstitution (CD4 + T cell at 144 weeks) in PLHIV on ART and that their persistent low concentrations were related to poor immune progression.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although some factors that have been traditionally linked to poor immune recovery are being investigated [3,5,24,28], the complete mechanism preceding ART-associated poor immune recovery remains unclear. On the basis of previous results [10,12,[29][30][31], we trust that adipokines may play a key role in immune reconstitution in PLHIV. Indeed, in this study, we postulated that low baseline circulating apelin receptor and ZAG concentrations were related to low CD4 + T-cell reconstitution (CD4 + T cell at 144 weeks) in PLHIV on ART and that their persistent low concentrations were related to poor immune progression.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, both adiponectin and omentin seem to exert both anti-inflammatory and pro-inflammatory effects according to the cell-specific differences in the adiponectin-and omentin-induced secretory process. Indeed, on the one hand, both adiponectin and omentin induce macrophage differentiation towards the M2 phenotype [31] and inhibit the secretion of inflammatory cytokines, such as TNFα and IL-6 [34][35][36][37]. On the other hand, adiponectin and omentin promote the secretion of pro-inflammatory cytokines (e.g., IL-6 [38,39], IL-1, IFNγ [40]) and chemokines (e.g., MIP1α [39]) from activated CD4 + T cells [40] and stimulate the activation of inflammatory pathways, such as NF-kB signaling, or the shift towards the M1 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that WAT could release hormones and adipokines to regulate appetite, metabolism and other organ functions (53)(54)(55). Some adipokines are reported to be related to hematopoiesis, such as leptin and adiponectin (56,57). Leptin and adiponectin are two important adipokines usually used as biomarkers for evaluating the endocrine function of adipocytes (58).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, tumor necrosis factor (TNF)-a, interleukin (IL)-6, and IL-1b play major roles in joint inflammation, and biological agents against these molecules have been developed in the field of RA therapy [1]. Adipokines are multifunctional signal transduction molecules, and their relationship with osteoimmunology has attracted attention in recent years [2][3][4][5][6][7][8][9][10][11]. In this review, we discuss the role and contribution of leptin, one of the best-characterized adipokines, in the pathogenesis of RA.…”
Section: Introductionmentioning
confidence: 99%